Investigating Strategies Used by the Teachers of SMK Negeri 1 Labuan and SMK Negeri 3 Palu in Enhancing Students’ Speaking Skills - Ningsih Markoh; Abdul Kamaruddin; Darmawan Darmawan (PALAPA, 2025)
This study examines the teaching strategies employed by English teachers at SMK Negeri 1 Labuan and SMK Negeri 3 Palu to enhance students’ speaking skills, addressing persistent challenges such as anxiety, low confidence, and limited vocabulary. The research aims to identify the strategies used, analyze their classroom implementation, and determine the most dominant approaches. Using a qualitative descriptive design, data were gathered from five English teachers through interviews, classroom observations, questionnaires, and documentation, and analyzed according to Oxford’s taxonomy of language learning strategies: memory, cognitive, compensation, metacognitive, affective, and social. The findings indicate that all six categories were applied to varying extents, with social and cognitive strategies most frequently and consistently used, followed by metacognitive and compensation strategies. Memory and affective strategies were employed less often but still contributed meaningfully to instruction. Teachers adapted these strategies to align with students’ needs, classroom contexts, and communicative objectives. The study concludes that strategy-based instruction, particularly through social interaction and emotional support significantly improves students’ speaking fluency, confidence, and participation. It underscores the importance of combining communicative practice with psychosocial readiness in vocational EFL settings, recommending continuous teacher training, curriculum alignment to foster learner autonomy, and further research incorporating student perspectives and mixed-method approaches.